2016
DOI: 10.1016/j.scitotenv.2016.05.101
|View full text |Cite
|
Sign up to set email alerts
|

Watershed-scale impacts of stormwater green infrastructure on hydrology, nutrient fluxes, and combined sewer overflows in the mid-Atlantic region

Abstract: Stormwater green infrastructure (SGI), including rain gardens, detention ponds, bioswales, and green roofs, is being implemented in cities across the globe to reduce flooding, combined sewer overflows, and pollutant transport to streams and rivers. Despite the increasing use of urban SGI, few studies have quantified the cumulative effects of multiple SGI projects on hydrology and water quality at the watershed scale. To assess the effects of SGI, Washington, DC, Montgomery County, MD, and Baltimore County, MD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(106 citation statements)
references
References 65 publications
1
96
1
Order By: Relevance
“…The LID design resulted in runoff volumes that were lower compared to non‐LID management and demonstrated LID's capacity to improve the catchment's water quality, specifically by decreasing catchment export of nitrate, ammonia, and total phsophorus . Pennino and others used measured hydrological and water quality data in multiple catchments (0.5–34.3 km 2 ) in the mid‐Atlantic coastal plain of the US and corroborated that stormwater LID—including rain gardens, detention ponds, bioswales, and green roofs—lowers the magnitude, frequency, and variability of stormwater runoff and decreases nitrate and TN export compared to catchments with limited LID implementations. In fact, when controlling for catchment size and percent impervious cover, catchments with higher percentages of LID implementation were found to have less flashy hydrological responses to storm events .…”
Section: Current Challenge: Scaling Local Lid To Catchment Responsesmentioning
confidence: 92%
See 1 more Smart Citation
“…The LID design resulted in runoff volumes that were lower compared to non‐LID management and demonstrated LID's capacity to improve the catchment's water quality, specifically by decreasing catchment export of nitrate, ammonia, and total phsophorus . Pennino and others used measured hydrological and water quality data in multiple catchments (0.5–34.3 km 2 ) in the mid‐Atlantic coastal plain of the US and corroborated that stormwater LID—including rain gardens, detention ponds, bioswales, and green roofs—lowers the magnitude, frequency, and variability of stormwater runoff and decreases nitrate and TN export compared to catchments with limited LID implementations. In fact, when controlling for catchment size and percent impervious cover, catchments with higher percentages of LID implementation were found to have less flashy hydrological responses to storm events .…”
Section: Current Challenge: Scaling Local Lid To Catchment Responsesmentioning
confidence: 92%
“…The goal of LID is to use plants, soils, and landscape design to control nonpoint sources of water and materials in built environments (Figure ; Table ), an approach that has become increasingly popular across communities worldwide as a cost‐effective way of managing stormwater pollution (e.g., runoff volumes and nutrient pollution) in urbanizing landscapes. For example, many municipalities across the mid‐Atlantic region of the United States (US) have a goal that 10–20% of the landscape drains through LID by 2030 . The increased interest in LID practices has led to a corresponding ascent in LID‐related research.…”
Section: Introductionmentioning
confidence: 99%
“…PP was 28% more effective at increasing shallow subsurface runoff and infiltration than RG. Recent studies point to a similar effectiveness of RG on water balance components at watershed scales [16,18]. Studies also have shown that PP can effectively mitigate surface runoff [57,58]; however, the degree of RG and PP functionality depends on the extent of the application area of LID within the watershed [59].…”
Section: Lid Practices and Watershed-scale Hydrological Effectsmentioning
confidence: 99%
“…The results from the subwatershed with smaller LID lots and underdrain connections showed a substantial reduction in peak discharge (up to 33%) and total storm runoff (up to 40%). Additionally, recent field-based research provides evidence of the cumulative watershed scale effects of LID on hydrologic responses, such as peak flows and pollutant loads [17][18][19][20]. Such experimental studies can be resource intensive (e.g., financial, personnel, time) [21]; however, process-based models provide a means to go beyond measured data and explore the projected "what if" LID scenarios using potentially less resources.…”
Section: Introductionmentioning
confidence: 99%
“…The no treatment zone/riparian zone in the LID watershed is exclusively riparian with no impervious cover and can be considered a nonstructural BMP in itself (Figure ). Although the LID watershed in our study has a relatively high amount of impervious surface cover as compared with LID design in other locations (Bedan and Clausen, ; Koch et al ., ; Duan et al ., ; Pennino et al ., ), BMPs in this LID watershed aimed to replicate natural hydrologic functioning. This replication was accomplished, in part, by infiltrating stormwater close to impervious surfaces that generate stormwater runoff (Bhaskar et al ., ) and included site‐specific LID goals as specified for Montgomery County Special Protection Areas (Montgomery County DEP, ).…”
Section: Methodsmentioning
confidence: 99%